Chronic dietary supplementation with soy protein improves muscle function in rats - Khairallah, Ramzi J.; O’Shea, Karen M.; Ward, Christopher W.; Butteiger, Dustie N.; Mukherjea, Ratna; Krul, Elaine S. (PLOS ONE, 2017)
Athletes as well as elderly or hospitalized patients use dietary protein supplementation to maintain or grow skeletal muscle. It is recognized that high quality protein is needed for muscle accretion, and can be obtained from both animal and plant-based sources. There is interest to understand whether these sources differ in their ability to maintain or stimulate muscle growth and function. In this study, baseline muscle performance was assessed in 50 adult Sprague-Dawley rats after which they were assigned to one of five semi-purified “Western” diets (n = 10/group) differing only in protein source, namely 19 kcal% protein from either milk protein isolate (MPI), whey protein isolate (WPI), soy protein isolate (SPI), soy protein concentrate (SPC) or enzyme-treated soy protein (SPE). The diets were fed for 8 weeks at which point muscle performance testing was repeated and tissues were collected for analysis. There was no significant difference in food consumption or body weights over time between the diet groups nor were there differences in terminal organ and muscle weights or in serum lipids, creatinine or myostatin. Compared with MPI-fed rats, rats fed WPI and SPC displayed a greater maximum rate of contraction using the in vivo measure of muscle performance (p<0.05) with increases ranging from 13.3–27.5% and 22.8–29.5%, respectively at 60, 80, 100 and 150 Hz. When the maximum force was normalized to body weight, SPC-fed rats displayed increased force compared to MPI (p<0.05), whereas when normalized to gastrocnemius weight, WPI-fed rats displayed increased force compared to MPI (p<0.05). There was no difference between groups using in situ muscle performance. In conclusion, soy protein consumption, in high-fat diet, resulted in muscle function comparable to whey protein and improved compared to milk protein. The benefits seen with soy or whey protein were independent of changes in muscle mass or fiber cross-sectional area.